KOMPONEN KIMIA MINYAK ATSIRIDAUN TIGA JENIS PIPERACEAE - Jamal, Yuliasri (BERITA BIOLOGI, 2002)
Chemical analysis of leaves essential oil on three Piper species, P. malamiri, P. baccatum and P. majusculum was conducted using gas chromatography and mass spectrometry (GCMS) method.Chromatogram result showed 52, 56 and 47 peaks on leaves essential oil of P.malamiri, P.baccatum and P.majusculum respectively. Based on the peaks,it is known that isocaryofilene is the major, common and as the highest component found in the three essential oils, beside several other major components.